PENDIDIKAN POLITIK BAGI CALON LEGISLATIF PEREMPUAN DI PROVINSI BANTEN (STUDI PADA BADAN PEMBERDAYAAN PEREMPUAN DAN MASYARAKAT DESA PROVINSI BANTEN) - Rahayu, Luis Fiska (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
The objectives of conducting this research were: first, to understand and analyze the operation of the Coordination, Advocacy, Facilitation, Outreach, and Evaluation mechanisms carried out by BPMD for women candidates; second, to discuss and analyze the extent of the efforts that have been made by BPPMD in carrying out its efforts, especially those concerning political education for female candidates in Banten Province. The theory used by researchers in conducting this research is the Theory of Political Education Institutions, while the research method used is a qualitative method with a descriptive analysis approach. The use of this qualitative method is because this method has advantages in understanding a phenomenon about what is experienced by research subjects such as behavior, perception, motivation, action holistically. Political education carried out by BPPMD, especially in the field of improving the Quality of Life for Women (PKHP) consists of breakthrough actions which include aspects of Coordination, Advocacy, Facilitation, Socialization and Evaluation which are abbreviated as KAFSE. Through this breakthrough action, BPPMD aspires to be able to improve the quality of female candidates in Banten Province. Based on the results of the research that has been done, the researcher concludes that improving the quality of female candidates is not an easy job and can be done in a short time, but is a long and continuous process. Even this effort is the responsibility of all parties, both the Government, Political Parties, Non-Governmental Organizations (NGOs), Religious and Community Organizations. BPPMD is making every effort so that there are funds from the State Budget that are allocated to improve the quality of life of women (Gender budgeting). However, it must be realized that there are still limitations in various ways, so that to achieve optimal results in accordance with the available facilities, infrastructure, and costs, even to achieve measurable targets and goals is very difficult to do.